2008
DOI: 10.1016/j.bbrc.2008.05.073
|View full text |Cite
|
Sign up to set email alerts
|

An RNA biding protein, Y14 interacts with and modulates STAT3 activation

Abstract: Signal transducer and activator of transcription 3 (STAT3), which mediates biological actions in many physiological processes, is activated by cytokines and growth factors via specific tyrosine phosphorylation, dimerization and nuclear translocation. To clarify the molecular mechanisms underlying the regulation of STAT3 activation, we performed yeast two-hybrid screening. We identified Y14, an RNA-binding protein, as a novel STAT3-binding partner. Y14 bound to STAT3 through the C-terminal region of STAT3 in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 24 publications
1
25
1
Order By: Relevance
“…RBM8A encodes Y14, an RNA binding protein that interacts with the C-terminal domain of STAT3 and RNA interference causes its downregulation in Hep3B cells incubated with interleukin-6. 36 Although, we did not observe altered expression in lymphoblastoid cell lines, it remains a candidate gene. Interestingly, TXNIP mRNA expression is increased 8-fold in megakaryocytes compared to in lymphoblastoid cell lines.…”
Section: Discussioncontrasting
confidence: 60%
“…RBM8A encodes Y14, an RNA binding protein that interacts with the C-terminal domain of STAT3 and RNA interference causes its downregulation in Hep3B cells incubated with interleukin-6. 36 Although, we did not observe altered expression in lymphoblastoid cell lines, it remains a candidate gene. Interestingly, TXNIP mRNA expression is increased 8-fold in megakaryocytes compared to in lymphoblastoid cell lines.…”
Section: Discussioncontrasting
confidence: 60%
“…Expression vectors, STAT3-LUC and STAT3-C were provided by Dr. T. Hirano (Osaka University, Osaka, Japan) and Dr. J. F. Bromberg (Rockefeller Univ., New York, NY), respectively [15,16]. Epitope-tagged Y14 and MAGOH was generated by PCR and sequenced (primer sequences are available upon request) [10].…”
Section: Methodsmentioning
confidence: 99%
“…The complex binds preferentially to spliced mRNAs immediately upstream of exon-junctions, and remains bound to the mRNAs after nuclear export [11,12]. In a previous study, we identified Y14 as a novel binding partner of STAT3 [10]. Y14 binds to STAT3 and affects IL-6-induced STAT3 transactivation by influencing the tyrosine-phosphorylation, nuclear accumulation and DNA-binding activity of STAT3.…”
Section: Introductionmentioning
confidence: 95%
“…Expression vectors for Y14, TNFR, NF-kB/p65, p50, p100, c-Rel, RIP1, TRADD, TRAF2/5, TAK1, NEMO, IKKa/b, IL-6 promoter-luciferase (pIL-6-LUC), and NF-kB-luciferase (NF-kB-LUC) were kindly provided by J. Inoue (Tokyo University, Tokyo, Japan), T. Kobayashi (Keio University, Tokyo, Japan), T. Fujita (Kyoto University, Kyoto, Japan), S. Akira (Osaka University), and H. Sakurai (Toyama University, Toyama, Japan) (22)(23)(24)(25). Expression vectors for Y14 were described previously (20,21). Anti-Y14, anti-MAGOH, anti-NF-kB/p65, anti-IkBa, anti-STAT3, anti-p300, anti-TRADD, and anti-Myc Abs were obtained from Santa Cruz Biotechnology (Santa Cruz, CA); anti-FLAG, anti-HA Abs were from Sigma-Aldrich (St. Louis, MO); anti-acetyl-NF-kB/p65 (Lys310), anti-pIkBa (Ser 32/36 ), and anti-pSTAT3 (Tyr 705 ) Abs were from Cell Signaling Technology (Beverly, MA); anti-RIP1 and anti-pSTAT3 (Ser 727 ) Abs were from GE Healthcare Life Sciences (Tokyo, Japan); anti-TRAF2 Ab was from AnaSpec (Fremont, CA); and anti-actin Ab was from Millipore (Billerica, MA).…”
Section: Reagents and Absmentioning
confidence: 99%
“…In Drosophila, the Y14-Mago homolog also participates in the transport and translational control of oskar mRNA during oogenesis (17)(18)(19). Although roles for Y14 have been actively examined with regard to mRNA control, we previously found that Y14 binds to a signaling molecule STAT3 (20). Notably, small interfering RNA (siRNA)-mediated reduction of endogenous Y14 expression in a hepatoma cell line (Hep3B) greatly decreased IL-6-induced tyrosine phosphorylation, nuclear accumulation, and DNAbinding activity of STAT3, as well as IL-6/STAT3-dependent gene expression.…”
mentioning
confidence: 99%